Trials to Overcome Drug Resistance to EGFR and ALK Targeted Therapies – Past, Present, and Future - Spaans, Johanna N.; Goss, Glenwood D. (Frontiers in Oncology, 2014)
Molecularly targeted agents (MTAs) are changing the therapeutic landscape in advanced non-small cell lung cancer (NSCLC). Since the discovery of sensitizing mutations in the epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) domain, clinical investigations have focused on optimizing the efficacy of EGFR and ALK tyrosine kinase inhibitors by addressing therapeutic resistance that commonly develops within a year of treatment initiation. Here, we review the clinical trials of novel therapies and combination regimens that have been undertaken in response to our evolving understanding of the mechanisms of resistance to therapy. The aim of these trials was to enhance the therapeutic efficacy of targeted therapies by improving targeted blockade and/or inhibiting parallel or compensatory signalling pathways. We have documented the sequential conduct of EGFR an ALK biomarker driven trials in order to highlight particular pitfalls and successes which should be considered in the design of future trials. Although there remain significant challenges, substantial gains have been made in our understanding of cellular resistance. This knowledge will drive the design of future trials, to the benefit of lung cancer patients.